2020
DOI: 10.3390/nano10091764
|View full text |Cite
|
Sign up to set email alerts
|

Developments in the Application of Nanomaterials for Water Treatment and Their Impact on the Environment

Abstract: Nanotechnology is an uppermost priority area of research in several nations presently because of its enormous capability and financial impact. One of the most promising environmental utilizations of nanotechnology has been in water treatment and remediation where various nanomaterials can purify water by means of several mechanisms inclusive of the adsorption of dyes, heavy metals, and other pollutants, inactivation and removal of pathogens, and conversion of harmful materials into less harmful compounds. To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(56 citation statements)
references
References 199 publications
(168 reference statements)
0
56
0
Order By: Relevance
“…Following the adsorption step, the filter and the ions retained therein can be disposed of or, more desirably, the filter can be recycled and the adsorbed species recovered [5,6]. A number of sorbent solids are usually employed, such as activated carbon, silica gel, pristine, and modified clay, activated silico-aluminates and polymeric materials [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the adsorption step, the filter and the ions retained therein can be disposed of or, more desirably, the filter can be recycled and the adsorbed species recovered [5,6]. A number of sorbent solids are usually employed, such as activated carbon, silica gel, pristine, and modified clay, activated silico-aluminates and polymeric materials [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several research groups have proposed the modification and the functionalization of carbon materials to achieve a satisfactory efficiency and selectivity [7,12]. The proposed functionalization processes are targeted to improve the coordination properties of carbon species in order to capture more easily the pollutants in the aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of polyurethane foam coated biogenic nanoparticles (current study) enables its reactivity rather than a basic physical barrier and achieves multiple goals in one integrated system. The persistence of nanomaterials in drinking water is of concern not only because of the economic cost of water recovery but also because of the potential health consequences of removing them from drinking water [88][89][90][91][92]. The biosynthesized foam coated nano silica silver nanoparticles (NSAgNPs) developed in the current study, showed complete reduction of microorganisms in contaminated tank water samples at optimal concentration (100 mg/L) and it does not have any detrimental effect on the treated water which encourages the incorporation of these nanoparticles into drinking water purification systems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TiO 2 nanocomposites are widely used as adsorbents to remove metal ions from industrial waste [43]. Therefore, the use of TiO 2 nanoparticles as adsorbent could be a promising solution for environmental remediation [44].…”
Section: Introductionmentioning
confidence: 99%